Advances in the Application of Traditional Chinese Medicine in the Rehabilitation of Gynecological Malignant Tumors - Zhao, Xiaoying; Li, Nan (Journal of Contemporary Medical Practice, 2026)
With advancements in treatment methods such as surgery, radiotherapy, and chemotherapy, the survival rate of gynecological malignant tumors has improved. Rehabilitation therapy for complications caused by the tumors themselves and related treatments has gradually become a focal point in the comprehensive care of female cancer patients. Due to the unique anatomical location and physiological functions of the uterus and ovaries, as well as the cyclical fluctuations of female hormones, patients with gynecological tumors are more susceptible to complications such as tumor-related depression, postoperative lymphedema (particularly following pelvic tumor surgery), and radiation-induced vaginitis (especially in cervical cancer patients). These complications threaten women’s physical and mental health and impact their recovery and resumption of normal life after surgery, radiotherapy, and chemotherapy. Leveraging its therapeutic principles of a holistic concept and syndrome differentiation, Traditional Chinese Medicine (TCM) has demonstrated favorable clinical efficacy in the rehabilitation treatment of complications associated with gynecological tumors. This article systematically reviews the recent advances (past five years) in the application of TCM in the rehabilitation of gynecological malignant tumors by retrieving relevant literature from multiple databases, aiming to provide a reference for the future TCM prevention and treatment of related complications.